Measuring Employment Standards Violations, Evasion and Erosion - Using a Telephone Survey - Noack, Andrea; Vosko, Leah; Grundy, John (Relations industrielles / Industrial Relations, 2015)
For many workers in Ontario, the Employment Standards Act (ESA) provides the only formal measures of workplace protection. The complaints-based monitoring system utilized by the Ontario Ministry of Labour, however, makes it difficult to assess the overall prevalence of employment standards (ES) compliance in the labour force. In addition to outright ESA violations, prevailing research highlights the significance of the erosion, evasion, and outright abandonment of ES for workers’ access to protection through practices such as the misclassification of workers and types of work. In this article, we report on efforts to develop a telephone-survey questionnaire that measures the overall prevalence of ES violations, as well as evasion and erosion in low-wage jobs in Ontario, without requiring respondents to have any pre-existing legal knowledge. Key methodological challenges included developing strategies for identifying ‘misclassified’ independent contractors, establishing measures for determining whether workers were exempt from the ESA, and translating the regulatory nuances embedded in the legislation into easy-to-answer questions. The result is a survey questionnaire unique in the Canadian context. Our questionnaire reflects the concerns of both academic researchers and workers’ rights activists. Pilot survey results show that Ontario workers do not necessarily distinguish between ES violations and other workplace grievances and complaints. With careful questionnaire design, it is nevertheless possible to measure the prevalence of ES violations, evasion and erosion. In order to track the effects of ES policies, particularly those on enforcement, we conclude by calling for the establishment of baseline measures and standardized reporting tools.